Death of the Author and the Question of the Legislative Intent - Geniušas, Saulius (Respectus Philologicus, 2003)
This paper is a hermeneutical investigation of a popular strategy among lawyers and philosophers of law, according to which an ambiguous legal norm can be resolved by reference to the legislative intention. Taking as its focus the way this theme unfolds in exclusive and inclusive legal positivism (more particularly, in the Marmor-Waldron debate), the paper calls for an abandonment of this strategy. The philosophical core of the paper is a discussion of the hermeneutical notion of the death of the author, which reveals the conceptual impossibility to question the intentions of the legislator. By bringing to a confrontation Ricoeur’s and Dworkin’s notions of interpretation, the paper shows why legal positivists are not to fear the separation of textual and psychological meanings: interpretation is not a subjectivistic projection of moral-political considerations and therefore it does not challenge the separation thesis. It does not contradict Raz’s argument from authority either. On the contrary, a conceptual possibility to question the legislator’s intent would render a number of Raz’s arguments baseless. A brief comparative analysis of Raz and Marmor reveals why, contra Waldron, there is no Raz-Marmor position: Marmor’s intentional thesis is self-defeating, for it does not work out the implications of Raz’s position but rather signifies its abandonment. In the final analysis, the hermeneutical theme of the death of the author reveals the fake nature of the never questioned presupposition in the Marmor-Waldron debate – the intentional thesis.